Farmer field school (FFS) approach to introduce rice farming and new rice production technologies to ex-combatant women in the Republic of Burundi - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Ex-combatant women were organized into groups and each group is provided land to grow rice on. The project supplied the necessary start-up finance for renting land, seed, and fertilizer while the women provided the labor. Using the farmer field school (FFS) approach, the women groups were provided advice and assistance from land preparation through to harvesting. Participatory variety selection (PVS) trials and other on farm trials in each group’s fields for collaborative research purposes were also conducted.